Nurses’ Communication in Providing Care for Children with Cancer: Literature Review - Dina Rasmita; Dewi Elizadiani Suza; Setiawan; Diah Arruum; Nurbaiti (Universitas Prima Indonesia, 2026)
Cancer in children presents a major global health problem, impacting not only the physical condition of pediatric patients but also causing significant psychological and social challenges for both the children and their families. Effective communication between nurses, children, and families is essential to ensure quality care, support psychosocial adaptation, and foster active involvement in decision-making. The study design used literature review. This literature review was conducted using PubMed, Scopus, and CINAHL (EBSCO) databases, focusing on articles published from 2014 to 2025. The inclusion criteria were English-language articles discussing nurse communication with children aged 0-18 diagnosed with cancer, with nurses as the main communicators, and full-text availability. The findings indicate that nurses assume multifaceted roles not only as providers of medical information, but also as emotional supporters, advocates, and key facilitators in multidisciplinary healthcare teams. Communication approaches identified include tailoring information to the child’s developmental stage and cultural context, validating emotions, and employing active listening, open-ended questioning, and reflection. However, nurses face considerable barriers such as limited time, insufficient communication training, unclear professional roles, emotional burden, and systemic challenges within healthcare settings. Therefore, there is a need to improve communication training, enhance institutional support, and develop policies that encourage multidisciplinary collaboration and a work environment that supports effective communication. These efforts are expected to strengthen the role of nurses in providing holistic, adaptive, and family-centered care in the pediatric oncology setting.